THE RELATIONSHIP BETWEEN ANXIETY LEVELS AND MENSTRUAL CYCLE DISORDERS IN UNDERGRADUATE NURSING STUDENTS WRITING THESES - Nurul Mu’jizah; Achmad Dafir Firdaus; Evi Dwi Prastiwi (Journal of Vocational Nursing)
Introduction: In the process of compiling a thesis, female students have a sense of anxiety. Anxiety that arises due to pressure and causes hormones that play a role in the menstrual cycle not to function properly, causing disorders in the menstrual cycle. The purpose of this study was to determine the relationship between anxiety levels and menstrual cycle disorders in female students of the Undergraduate Nursing Study Program who are compiling theses at Maharani Health College (STIKes Maharani).  Methods: The research design used was Cross-sectional. Sampling used a purposive sampling technique. The research sample was 40 respondents. Data were collected by distributing questionnaires adopted from previous research that had undergone validity and reliability tests. Results: The results of this study found data on the highest level of anxiety, namely 31 people (77.5%) with moderate anxiety levels and 21 people (52.5%) experiencing menstrual cycle disorders. Based on the Fisher Exact Test, the p-value was obtained = 0.046 <α (0.05). Conclusions: It was concluded that there was a relationship between anxiety levels and menstrual cycle disorders in female students of the Undergraduate Nursing Study Program who were compiling theses at STIKes Maharani. Anxiety often causes menstrual cycles to become irregular. It is hoped that the anxiety experienced by female students while writing their thesis can be anticipated by adapting to their individual levels of anxiety. Female students must also have positive coping adaptations so that they do not have an impact on physiological changes and menstrual cycle disorders.